1972
DOI: 10.1128/aac.2.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Properties of Polymyxin B and Its Potentiation of Tetracycline as an Antifungal Agent

Abstract: High concentrations of polymyxin B inhibited the growth of Candida albicans and Saccharomyces cerevisiae. When these yeasts were incubated with concentrations of polymyxin B too low to affect growth, and were then exposed to tetracycline, protein synthesis was inhibited and at least 99% of the organisms were killed. Neither inhibition of protein synthesis nor cell death occurred in cultures treated with high concentrations of tetracycline alone. We conclude that polymyxin B at high concentrations affects the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 7 publications
3
37
0
Order By: Relevance
“…5, allicin did not induce a plasma membrane permeability change in yeast cells, as judged from the extents of their leakages at the control levels. In agreement with the previous reports [6,7], PMB enhanced the release of UV-absorbing materials to a considerable extent, but its release was kept at lower level than cells treated with Triton X-100 (Fig. 5a).…”
Section: Allicin-dependent Fungicidal Activity Of Pmb Against S Ceresupporting
confidence: 82%
See 1 more Smart Citation
“…5, allicin did not induce a plasma membrane permeability change in yeast cells, as judged from the extents of their leakages at the control levels. In agreement with the previous reports [6,7], PMB enhanced the release of UV-absorbing materials to a considerable extent, but its release was kept at lower level than cells treated with Triton X-100 (Fig. 5a).…”
Section: Allicin-dependent Fungicidal Activity Of Pmb Against S Ceresupporting
confidence: 82%
“…PMB passing through the outer membrane interacts with the acidic phospholipids exposed on the plasma membrane, and thus, its lethal action is proposed to depend on the increase in the plasma membrane permeability to intracellular molecules [1,5]. PMB can also interact with the plasma membranes of Saccharomyces cerevisiae and Candida albicans, as seen from its stimulatory effect on the membrane permeability to various antibiotics such as tetracycline, miconazole, and ketoconazole [6,7]. However, it remains unknown why the fungicidal activity of PMB is much lower than its bactericidal activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative bacteria have generally been found to be more sensitive to polymyxins than gram-positive bacteria (26,35), whereas only a few studies on yeasts have reported antagonistic activity of these antibiotics against fungi (33,35). Our results show that polymyxin B also has an antifungal activity against Fusarium spp.…”
Section: Discussionsupporting
confidence: 64%
“…2 In addition, when yeast cells are incubated with PMB at the concentration too low to affect their growth in the presence of various antibiotics, for instance tetracycline or miconazole, PMB increases the permeability of plasma membrane to each antibiotic and their combinations can induce cell death. [3][4][5] In our recent study, PMB was found to cause vacuolar membrane-disruptive damage in Saccharomyces cerevisiae cells when this bactericidal antibiotic is added alone at a high concentration and also at a non-lethal concentration in combination with allicin (Figure 1), an allyl sulfur compound from garlic. 6 The vacuole-disruptive damage in fungi was first observed when S. cerevisiae cells were treated with a polyol macrolide antibiotic niphimycin (NM).…”
Section: Introductionmentioning
confidence: 99%